Transvenous embolization of hemorrhagic brain arteriovenous malformations: Case reports and literature review - Chen, Xiheng; Zhang, Longhui; Zhu, Haoyu; Wang, Yajie; Fan, Liwei; Ni, Leying; Dong, Linggen; Lv, Ming; Liu, Peng (Frontiers in Neurology, 2022)
Transvenous embolization with good clinical outcomes emerged as a novel concept in the contemporary management of brain arteriovenous malformations. Here, we presented four cases of hemorrhagic brain AVMs who underwent the endovascular treatment via transvenous approach in our center between July 2019 and July 2020. We retrospectively collected and analyzed demographics, medical history, clinical presentation, imaging results and clinical and angiographic follow-up data among all patients in detail. three patients (75%) were independent (mRS ≤2) at discharge and all four patients were independent at last follow-up. Clinical cure was achieved in all four patients with hemorrhagic brain AVMs via a transvenous approach. Here, we shared our experience in this context and conducted a review of relevant literatures.